Efficacy and safety of LiWei capsule in chronic non-atrophic gastritis with erosions: a randomized controlled trial - Danyang Cui; Xiao Geng; Juan Wang; Xu Han; Zhijun Huang; Miao Jiang; Yang Gong (Scientific Reports)
Abstract To assess the efficacy and safety of LiWei Capsule (LWC) in the treatment of chronic non-atrophic gastritis (CNG) with erosions and damp-heat stasis syndrome, based on Traditional Chinese Medicine (TCM) principles. This phase II, multicenter, randomized, double-blind, placebo- and positive-controlled trial enrolled patients diagnosed with CNG with erosions and damp-heat stasis syndrome. Participants were allocated to LWC, Sanjiu Weitai Capsule (SJWT, positive control), and placebo groups (2:1:1 ratio) and received corresponding treatment for 4 weeks, followed by a 16-week follow-up. The primary outcome was the curative rate of epigastric pain/bloating. Secondary outcomes included improvement in endoscopic examination, histopathological examination, and TCM symptom scores. Of 301 enrolled participants from five centers, 189 completed the study (95, 45, 49 cases in LWC, SJWT, and placebo groups, respectively). After 4 weeks of treatment, the curative rates of epigastric pain/bloating were 76.84%, 42.22%, and 22.45% in LWC, SJWT, and placebo groups, respectively (P < 0.001). The healing rates of endoscopic erosions were 65.3%, 46.7%, and 30.6% in LWC, SJWT, and placebo groups, respectively (P < 0.001). LWC effectively and safely alleviates epigastric pain/bloating and promotes endoscopic erosion healing in CNG patients with erosions (damp-heat stasis syndrome). LWC may be a promising treatment option for this condition. Trial registration: ChiCTR2100052010, assigned by the Chinese Clinical Trial Registry, registration date 13/10/2021.